2014
DOI: 10.1039/c3bm60248f
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin-matrix sandwich-like microenvironments to manipulate cell fate

Abstract: Conventional 2D substrates fail to represent the natural environment of cells surrounded by the 3D extracellular matrix (ECM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…[22a,46b] FN in its globular conformation is unable to adequately facilitate cellular binding to adhesion and growth factor domains present on the molecule, while when adsorbed on PEA as nanonetworks it exposes these binding sites and enhanced cellular adhesion and signaling occur. [17a,47] Previous studies have showed that unmodified semicrystalline PLLA is unable to induce such structural changes in adsorbed FN, as we have confirmed here (Figure A). Indeed, while HFN7.1 antibodies are able to bind near the RGD domain on globular FN, as found on unmodified PLLA, only the structural conformation change provided by the addition of PEA brushes is able to expose the synergy binding domain recognized by mAb1937 (Figure F).…”
Section: Discussionmentioning
confidence: 83%
“…[22a,46b] FN in its globular conformation is unable to adequately facilitate cellular binding to adhesion and growth factor domains present on the molecule, while when adsorbed on PEA as nanonetworks it exposes these binding sites and enhanced cellular adhesion and signaling occur. [17a,47] Previous studies have showed that unmodified semicrystalline PLLA is unable to induce such structural changes in adsorbed FN, as we have confirmed here (Figure A). Indeed, while HFN7.1 antibodies are able to bind near the RGD domain on globular FN, as found on unmodified PLLA, only the structural conformation change provided by the addition of PEA brushes is able to expose the synergy binding domain recognized by mAb1937 (Figure F).…”
Section: Discussionmentioning
confidence: 83%
“…The stimulation of dorsal receptors within the sandwich-like culture triggers changes in cell morphology, cell adhesion and intracellular signaling pathways (e.g. focal adhesion kinase, FAK) [10][11][12] . As an example, fibroblasts cultured within the sandwich-like system overexpressed the α 5 integrin subunit compared to the 2D, as observed for other 3D cultures 15,16 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…We, among others, have been involved in the research of new alternatives for sandwich cultures, such as the use of ventral and dorsal surfaces with different properties/characteristics (e.g., stiffness and/or topological patterns) (Ballester-Beltrán et al, 2015). This system has shown cell morphology to be related to substrate rigidity and the ability of cells to reorganize ECM proteins adsorbed to these surfaces (Beningo et al, 2004;Ballester-Beltran et al, 2012b;Ballester-Beltrán et al, 2014). Furthermore, it has been shown that sandwich-like cultures can modify cell spreading/elongation and migration rates depending on the substrates properties, resulting in closer 3D environment behaviors (Beningo et al, 2004;Ballester-Beltrán et al, 2015).…”
Section: Solid Phase Stimulationmentioning
confidence: 99%